Let $(E,\mathcal E,\mu)$ be a measure space and $A$ be a self-adjoint bounded linear operator on $L^2(\mu)$. Assume $Af\ge0$ for all $f\in\mathcal L^2(\mu)$ with $f\ge0$. Let $$c_1:=\sup_{\substack{f\in\mathcal L^2(\mu)\setminus\{0\}\\f\ge0}}\frac{\left\|Af\right\|_{L^2(\mu)}}{\left\|f\right\|_{L^2(\mu)}}.$$

I would like to show that $$c_1=\sup_{\substack{f\in\mathcal L^2(\mu)\setminus\{0\}\\f\ge0}}\frac{\langle Af,f\rangle_{L^2(\mu)}}{\left\|f\right\|_{L^2(\mu)}^2}=:c_2.\tag1$$

Note that this is a classical result which is true when the suprema in the definitions of $c_1$ and $c_2$ are taken over $\mathcal L^2(\mu)\setminus\{0\}$ and we take the absolute value of the inner product in the definition of $c_2$.

Mimicing the usual proof, we easily obtain $$c_2\le c_1=\sup_{\substack{f,\:g\:\in\:\mathcal L^2(\mu)\\\left\|f\right\|_{L^2(\mu)}\:=\:\left\|g\right\|_{L^2(\mu)}\:=\:1\\f,\:g\:\ge\:0}}\langle Af,g\rangle_{L^2(\mu)}=:c_3\tag2.$$ Now we the classical claim (without the nonnegativity condition in the domain over which the supremum is taken in the definition of $c_3$) is concluded by showing $$c_3\le c_2\tag3$$ using the parallelogram law. Obviously, the problem with this is that the difference of nonnegative functions doesn't need to be nonnegative. Can we fix this or conclude by a different argument?

  • $\begingroup$ I saw your question yesterday, and it motivated me to think of this question, I have no answer, good question anyway. $\endgroup$ – user284331 Dec 7 '19 at 20:31
  • $\begingroup$ @user284331 If $\kappa$ is any transition kernel, then $\kappa f\ge0$ whenever $f\ge0$. Simply cause $(\kappa f)(x)=(\kappa(x,\;\cdot\;)f$ is the integral of a nonnegative function with respect to a nonnegative measure. In your situation, $K$ could be the density of a transition kernel with respect to the Lebesgue measure. $\endgroup$ – 0xbadf00d Dec 7 '19 at 20:34
  • $\begingroup$ @user284331 Regarding the ordering: It's the same as the one given on a general Hilbert lattice. $\endgroup$ – 0xbadf00d Dec 7 '19 at 20:38
  • $\begingroup$ I suspect that there is something wrong with the question as stated. Unless I misunderstand something, if you know $(2)$ then the thing you'd want to prove is that $c_1 \leq c_3$. To do this, it'd be enough to show that for $f \geq 0$ with $\|f\| = 1$ we have that $\|Af\| \leq c_3$. If $Af = 0$ this is trivial. Otherwise, we can take $g = \|Af\|^{-1} Af$ to see that $\|Af\| \leq \langle Af, g \rangle \leq c_3$. Maybe the $\sup$ in $c_3$ is meant to be taken over non-negative functions or something? $\endgroup$ – Rhys Steele Dec 7 '19 at 21:23
  • $\begingroup$ @RhysSteele Maybe you were confused since I wrote $c_1\ge c_2$ (instead of $c_2\le c_1$); otherwise I don't know what you mean. If $(2)$ holds, then $c_2\le c_1=c_3$. So, if we can show that $c_3\le c_2$, we need to have $c_1=c_2$. $\endgroup$ – 0xbadf00d Dec 8 '19 at 5:29

I assume that the complex Hilbert space $L^{2}(\mu)$ is in issue, so the definition of $c_{2}$ and $c_{3}$ are respectively \begin{align*} c_{2}=\sup_{f\geq 0,~\|f\|=1}\left<Af,f\right>_{r}, \end{align*} and that \begin{align*} c_{3}=\sup_{f,g\geq 0,~\|f\|=\|g\|=1}\left|\left<Af,g\right>\right|, \end{align*} where \begin{align*} \left<f,g\right>=\int f\overline{g}, \end{align*} and that \begin{align*} \left<f,g\right>_{r}=\int fg. \end{align*}

Let $f,g\geq 0$, $\|f\|=\|g\|=1$ be given. First of all, since $A(f)\geq 0$, it is trivial that $\left<Af,f\right>_{r}=\left<Af,f\right>$ and $\left|\left<Af,g\right>\right|=\left<Af,g\right>\geq 0$, so there is no need to distinguish $\left<\cdot,\cdot\right>_{r}$ and $\left<\cdot,\cdot\right>$ in the definition of $c_{2}$ and $c_{3}$. The absolute value in $c_{3}$ can also be removed.

We know the formula that \begin{align*} 4\text{Re}\left<Af,g\right>=\left<A(f+g),f+g\right>-\left<A(f-g),f-g\right>. \end{align*} But in this case, the term $\text{Re}\left<Af,g\right>$ simply becomes $\left<Af,g\right>$.

Now we let $h=f-g$, the crucial point is to realize that \begin{align*} |A(h)|\leq A(|h|). \end{align*} Indeed, since $h$ is real-valued, we have $|h|+h\geq 0$. Since $h=h^{+}-h^{-}$, linearity of $A$ gives $Ah=Ah^{+}-Ah^{-}$. Keep in mind that both $Ah^{+},Ah^{-}\geq 0$, so $Ah$ is real-valued.

As $A$ is order-preserving, we have $A(|h|+h)\geq 0$, linearity of $A$ and the fact that $Ah$ being real-valued give $A(|h|)\geq-A(h)$. The same account applies to $|h|-h\geq 0$ to get $A(|h|)\geq A(h)$.

As a result, \begin{align*} \left|\left<A(f-g),f-g\right>\right|\leq\left<|A(f-g)|,|f-g|\right>\leq\left<A(|f-g|),|f-g|\right>. \end{align*} We obtain that \begin{align*} & 4\left<Af,g\right>\\ &\leq\|f+g\|^{2}\left|\left<A\left(\dfrac{f+g}{\|f+g\|}\right),\dfrac{f+g}{\|f+g\|}\right>\right|+\|f-g\|^{2}\left|\left<A\left(\dfrac{|f-g|}{\|f-g\|}\right),\dfrac{|f-g|}{\|f-g\|}\right>\right|\\ &=\|f+g\|^{2}\left<A\left(\dfrac{f+g}{\|f+g\|}\right),\dfrac{f+g}{\|f+g\|}\right>+\|f-g\|^{2}\left<A\left(\dfrac{|f-g|}{\|f-g\|}\right),\dfrac{|f-g|}{\|f-g\|}\right>\\ &\leq c_{2}(\|f+g\|^{2}+\|f-g\|^{2})\\ &= 2c_{2}(\|f\|^{2}+\|g\|^{2})\\ &= 4c_{2}, \end{align*} so $\left<Af,g\right>\leq c_{2}$, and hence $c_{3}\leq c_{2}$ is claimed.

  • $\begingroup$ Thank you! What you wrote is indeed the crucial point. The rest is the same as for the standard result. $\endgroup$ – 0xbadf00d Dec 10 '19 at 15:31
  • $\begingroup$ Note that the first equality after "We obtain that" should be "$\le$". $\endgroup$ – 0xbadf00d Dec 10 '19 at 15:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.